151k views
3 votes
Solve the following:
6-(-7)=
15+9-8=
18-(-9)=
3+(-3)=
-2+4=

User Orlymee
by
4.9k points

1 Answer

4 votes

Answer:

1. 13

2. 16

3. 27

4. 0

5. 2

Explanation:

1. 6-(-7) becomes 6+7 because subtracting a negative number is the same as adding that positive number

2. simple, add 15+9 and then subtract 8

3. the same thing as #1, 18-(-9) becomes 18+9

4. 3+(-3) becomes 3-3 because adding a negative number is the same as subtracting the number

5. may be simpler if you reorder the equation in your head like "4-2"

User Shen Yudong
by
5.4k points